2021
DOI: 10.1016/j.heliyon.2021.e07291
|View full text |Cite
|
Sign up to set email alerts
|

Genomic insights into the sessile life and biofouling of barnacles (Crustacea: Cirripedia)

Abstract: Members of the infraclass Cirripedia, commonly called barnacles, are unique among the subphylum Crustacea in that they exhibit a biphasic life cycle with a planktonic larval stage and a sessile adult stage. Understanding their unique sessile life and mechanisms of attachment are hampered by the lack of genomic resources. Here, we present a 746 Mb genome assembly of Lepas anserifera – the first sequenced stalked barnacle genome. We estimate that Cirripedia first arose ~495 million years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 101 publications
(106 reference statements)
1
7
0
Order By: Relevance
“…The quality of the sequence data was assessed with fastp software (Chen et al, 2018 ). The genome of L. anserifera (Cirripedia, Lepadidae) (Ip et al, 2021 ) was used as a reference genome and clean data were aligned to the genome with BWA (Li & Durbin, 2010 ). SNP calling was conducted using Samtools (Danecek et al, 2021 ) and the outputs were put into gstacks program (−‐rm‐unpaired‐reads) in Stacks to build loci and identify SNPs by incorporating paired‐end reads.…”
Section: Methodsmentioning
confidence: 99%
“…The quality of the sequence data was assessed with fastp software (Chen et al, 2018 ). The genome of L. anserifera (Cirripedia, Lepadidae) (Ip et al, 2021 ) was used as a reference genome and clean data were aligned to the genome with BWA (Li & Durbin, 2010 ). SNP calling was conducted using Samtools (Danecek et al, 2021 ) and the outputs were put into gstacks program (−‐rm‐unpaired‐reads) in Stacks to build loci and identify SNPs by incorporating paired‐end reads.…”
Section: Methodsmentioning
confidence: 99%
“…46 Besides, the expansion and specific expression of genes in the peduncle of stalked barnacles are suggested to contribute to the permanent attachment of Lepas anserifera. 22 Parasitic lifestyle: Several classes of Crustacea contain parasites, including Cirripedia, Copepoda and Malacostraca, which are critical players in aquatic ecosystem dynamics. 91 Comparative genomics has demonstrated that parasites exhibit an apparently reduced number of protein-coding genes compared to free-living species.…”
Section: Lifestylementioning
confidence: 99%
“…Only four species of Thoracica and one species of Rhizocephala have published genomes (Table 1). These four economic species of Thoracica include two sessile barnacles ( Amphibalanus amphitrite and Semibalanus balanoides ) and two stalked barnacles ( Pollicipes pollicipes and Lepas anserifera ) with contig or scaffold N50 lengths ranging from 56 Kb to 670 Kb 21–23 …”
Section: Summary Of Published Crustacean Genomesmentioning
confidence: 99%
“…In addition, changes in Hox gene expression have generated morphological differences between Crustacean species, which could be responsible for the evolutionary history of this group (Abzhanov & Kaufman, 2000a, 2000bAverof & Patel, 1997;Liubicich et al, 2009;Martin et al, 2016). Ten Hox genes has been identified in crustaceans, such as in Litopenaeus vannamei (Sun et al, 2015), Penaeus monodon (Uengwetwanit et al, 2021), Daphnia pulex, and Daphnia magna (D. H. Kim et al, 2018;Pace et al, 2016), while nine Hox genes have been identified in Paracyclopina nana (H. S. Kim et al, 2016), Exapalomon carinicauda (Yuan et al, 2017), P. hawaiensis (Serano et al, 2016), and Lepas anserifera (Ip et al, 2021). However, the identification and expression of Hox genes during development of crustacean decapods has been limited to P. hawaiensis (Martin et al, 2016), Procambarus clarkii (Abzhanov & Kaufman, 2000a, 2000b, L. vannamei (Li et al, 2012;Sun et al, 2015), and Eriocheir sinensis (Cui et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Ten Hox genes has been identified in crustaceans, such as in Litopenaeus vannamei (Sun et al, 2015), Penaeus monodon (Uengwetwanit et al, 2021), Daphnia pulex , and Daphnia magna (D. H. Kim et al, 2018; Pace et al, 2016), while nine Hox genes have been identified in Paracyclopina nana (H. S. Kim et al, 2016), Exapalomon carinicauda (Yuan et al, 2017), P . hawaiensis (Serano et al, 2016), and Lepas anserifera (Ip et al, 2021). However, the identification and expression of Hox genes during development of crustacean decapods has been limited to P .…”
Section: Introductionmentioning
confidence: 99%